Beyond spectrum: the digital photography book / Sharifah Shaari ... [ et al.] - Shaari, Sharifah; Abdul Samat, Raziq; Wan Mohd Zain, Wan Nor Ayuni; Madon, Dona Lowii; Mohd Sharif, Nadzri (Universiti Teknologi MARA, Perak, 2020)
The digital photography book - is a compilation of articles from lecturers and selected best artwork from final year students program Diploma in Photography & Creative Imaging, Faculty of Art & Design, UiTM Cawangan Melaka. There are 12 articles written by the lecturer based on the topic in photography; the content is related to what students have learned throughout their studies at the diploma level. Objective of this book is to make innovation through visualization – from ordinary exhibition artwork into book, to show best artwork from final year students Program Diploma in Photography & Creative Imaging, Faculty of Art & Design, UiTM Cawangan Melaka, and to produce academic book for commercial purpose. This book actually inspired from the final year diploma show exhibition of Art & Design Student, UiTM cawangan Melaka. Each of the students try their best to produce the artwork based on the project given as a part of their task to complete the studies. What makes this book special because beside the student artwork, this book also includes one article from the Head of Faculty and 11 articles from the lecture Department of Photography & Creative Imaging, UiTM cawangan Melaka. All the articles from various topics but all of it relate to the photography field. Hopefully Beyond Spectrum - the digital photography book can be used as guidance for other new final year students Program Diploma Photography & Creative Imaging and new beginner photographers who want to know detail about the photography field.